2014
DOI: 10.1007/s10823-014-9254-5
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Living Arrangements in Myanmar and Thailand: A Comparative Analysis

Abstract: The present study compares living arrangements and related intergenerational support in Myanmar and Thailand based on recent national surveys of older persons in both countries and prior surveys in Thailand. The countries share relatively similar cultural contexts but differ radically in economic development. Substantially higher percentages of older persons in Myanmar currently coreside with their children and are considerably more likely to have non-coresident children living in the same locality. They are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…In Thai culture, parents, children, and grandchildren traditionally live together, and many elderly people retain a role of caregiver to their grandchildren within these intergenerational families. 32 Moreover, a recent study reported that such intergenerational families are common to countries such as Thailand, Myanmar, and Vietnam. 32 Many children may migrate to work outside their native province, for example, for career development, yet they can keep in touch with their parents due to the increasing use of mobile phones, as well as improved road access and transportation in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…In Thai culture, parents, children, and grandchildren traditionally live together, and many elderly people retain a role of caregiver to their grandchildren within these intergenerational families. 32 Moreover, a recent study reported that such intergenerational families are common to countries such as Thailand, Myanmar, and Vietnam. 32 Many children may migrate to work outside their native province, for example, for career development, yet they can keep in touch with their parents due to the increasing use of mobile phones, as well as improved road access and transportation in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…Some Asian countries too, experienced lower fertility rates as compared to a few decades ago. In Thailand for example, older people who were childless in 2011 was at 6 to 7 percent, doubling the figure from 1986 (Knodel & Pothisiri, 2015).…”
Section: Previous Studies On Childlessnessmentioning
confidence: 97%
“…The extended family unit typically consists of the older couple, sons, their wives and families, and unmarried daughters. Living arrangements and related intergenerational support are essentially relationships based on specific duties and responsibilities (Bowen 2002, Joseph 2000, Knodel 2015, Newcomb 2009, Rugh 1984. In some 17 As an ethical strategy to protect the study subjects' confidentiality, brief profiles of gender boundaries are outlined in general terms within geographic regions that include countries where they originate from rather than providing a description of how gender roles looked like in each specific country of origin.…”
Section: Research Objectivesmentioning
confidence: 99%
“…areas, such as the Middle East, ethnic relations often contributed to survivalist mentality among the minorities (Rugh 1984); and in some areas such as Southeastern Asia, although parents treasure their daughters, they favor their sons (Knodel 2015).…”
Section: Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation